Macrolichens from central West Greenland - Hansen, Kjeld (Meddelelser om Grønland, 1962)
The present paper deals with collections and studies of lichens, carried out by the author on a botanical expedition to the central parts of West Greenland in 1958. In an introductory chapter a survey is taken of the most significant earlier collections of, and papers on, lichens from this part of Greenland. In a list of the 44 localities visited by the expedition (fig. 1, p. 11), located between Sukkertoppen, ea. 65° lat. N., and the northeastern part of Disko Bugt, ea. 70° lat. N., various information is given of the individual localities, thus of their position, the number of lichens collected, the altitude above sea-level at which the collections were made, and the time for the stay of the collector. The localities investigated are situated in areas which differ greatly in an ecological and a floristic respect, and the localities are therefore grouped in districts in accordance with BÖCHER, HOLMEN & JAKOBSEN (1957, 1959). During the expedition a greatly varying number of lichen samples, totalling ea. 1800, were collected in the majority of the 44 localities, and in addition ea. 500 lichens derived from the vegetation analyses made were brought home for identification. Only the macrolichens are dealt with in the present paper, for owing to the very limited time at our disposal in the various localities only comparatively few and scattered collections of microlichens were made. In the systematic part of the paper all the localities in which the individual species were collected are given for each of the 108 species treated here, the localities being arranged according to their position in the five floristic districts. Information is likewise given of the altitude of the locality above the sea, and as to whether apothecia were found in the rarely fertile species. As for the majority of the taxa, brief particulars are given of other special biological conditions and of their distribution in Greenland previously known. The greater number of the species had formerly been reported from the region of Greenland dealt with here, but as to many of them the samples recorded here have caused a considerable shifting of their known distribution in West Greenland. In the concluding chapters an account is given of some characteristic features of the lichen vegetation in some selected localities within the five floristic districts. As regards several lichen communities a relation to ecological factors, climatic as well as edafic, can be demonstrated. Finally, a survey is taken of species with a continental or oceanic, and a northern or southern distribution in West Greenland.